Testing for thyroid hormone disruptors, a review of non-mammalian in vivo models. (15th May 2020) - Couderq, Stephan; Leemans, Michelle; Fini, Jean-Baptiste
Abstract: Thyroid hormones (THs) play critical roles in profound changes in many vertebrates, notably in mammalian neurodevelopment, although the precise molecular mechanisms of these fundamental biological processes are still being unravelled. Environmental and health concerns prompted the development of chemical safety testing and, in the context of endocrine disruption, identification of thyroid hormone axis disrupting chemicals (THADCs) remains particularly challenging. As various molecules are known to interfere with different levels of TH signalling, screening tests for THADCs may not rely solely on in vitro ligand/receptor binding to TH receptors. Therefore, alternatives to mammalian in vivo assays featuring TH-related endpoints that are more sensitive than circulatory THs and more rapid than thyroid histopathology are needed to fulfil the ambition of higher throughput screening of the myriad of environmental chemicals. After a detailed introduction of the context, we have listed current assays and parameters to assess thyroid disruption following a literature search of recent publications referring to non-mammalian models. Potential THADCs were mostly investigated in zebrafish and the frog Xenopus laevis, an amphibian model extensively used to study TH signalling. Highlights: Testing for thyroid hormone (TH) disruptors is particularly challenging due to the lack of validated in vitro assays. In contrast to rodent models, amphibian and teleost embryos or larvae are amenable to higher throughput screening. Xenopus laevis is employed in several validated and standardized assays to investigate the effects of TH axis disrupting chemicals. The zebrafish ( Danio rerio ) is a promising alternative vertebrate model to examine disruption of TH signalling. Further studies are needed to implement neurodevelopmental and behavioural endpoints mediated by TH signalling.